SATISFACTION LEVEL ANALYSIS TOWARDS QUALITY SERVICE OF PHARMACY INSTALLATION IN SETJONEGORO HOSPITAL WONOSOBO - Tiyas Putri Nughaheni; Achmad Purnomo (JURNAL MANAJEMEN DAN PELAYANAN FARMASI (Journal of Management and Pharmacy Practice))
In order to face globalization, hospital as an institution that specializes in health services should pay moreattention to aspects of satisfaction for service users or patients. The vision of this study is to know the quality ofservice, the gap between expected service quality of patients with perceived service quality, and to know prioritasimprovement servqual dimensions that must be done to increase customer satisfaction according to customerinterests.This research is descriptive case study research. Respondents in this study were the customer of IFRJ Setjonegoro Wonosobo hospitals, as many as 120 patients. Respondents consisted of 30 general patients, 30 Askes patients, 30Jamsostek patients and 30 Jamkesmas patients. Data were analyzed using weighted SERVQUAL model Cronin and Taylor, gap analysis and important performance analysis.The results of this study indicate that the quality of care in Pharmacy Departement Setjonegoro Wonosobohospitals already has satisfy the external customer, among in general patient services, Askes patients, Jamsostekpatients andJamkesmas patients. The biggest gap according to the General largest on assurance dimension, while according to the Askes and Jamsostek patient is the dimension of responsiveness, according to Jamkesmaspatients are at the tangible dimension. According to important-performance matrix in Quadrant I (priority)is the dimension of responsiveness (patient Askes), tangible dimensions (Jamsostek and Jamkesmas patients),Quadrant II (sustained performance) is a tangible dimension, responsiveness and assurance (General patients),tangible dimension , reliability and assurance (Askes patients), assurance and responsiveness dimensions (patientJamsostek), and the dimensions of responsiveness (patient Jamkesmas), Quadrant III (low priority) is the dimension of empathy (General patients and patients Askes), Quadrant IV (excessive service) is the dimension of reliability (General patients), dimensions of reliability and empathy (Jamsostek patients), and the dimensions reliability,assurance and empathy (Jamkesmas patients). Keywords: Quality of Service, Gap, Important-Performance Analysis.